Pengajaran Komunikasi Jaringan dengan Metode Flipped Classroom - Zulkipli, Zulkipli; Aranbi, Muhammad Defa; Putri, Lara Aulia; Isnain, M. Firdaus; Wea, Yohanes Emanuel Dala (Indo-MathEdu Intellectuals Journal, 2025)
Teaching network communication has become an important competency in the digital era, especially for students in technology fields and prospective educators. This study aims to evaluate the effectiveness of the flipped classroom method in enhancing conceptual understanding and student engagement in the course of Network Communication. The research employs a quasi-experimental design involving 60 fourth-semester students from the Computer Engineering study program at a private university in Indonesia. Data were collected through pretests and posttests, observation of student activities, and a classroom engagement questionnaire. The results show that the level of learning completeness increased from 5.00% in the pretest to 66.67% in the posttest after the implementation of the flipped classroom method. In addition, 83.33% of students were classified as fairly active and 15.00% active during the learning process. This improvement in learning outcomes and activity indicates that the flipped classroom method has a positive impact on student engagement and understanding. This approach not only strengthens digital literacy and independent learning, but also encourages the creation of active, interactive, and humanistic learning.